Japanese Papaya (Cnidoscolus aconitifolius): An Integrated Biological System with Mechanism-Based Utilization - Sedijani, Prapti; Mahrus, Mahrus; Rasmi, Dewa Ayu Citra; Kusmiyati, Kusmiyati; Khaerudin, Khaerudin (Jurnal Biologi Tropis, 2025)
Cnidoscolus aconitifolius (Japanese papaya or chaya) is a tropical plant from the Euphorbiaceae family known for its high nutritional value and diverse biological activities. Several studies have reported antioxidant, antimicrobial, and other biological properties, suggesting the involvement of complex molecular systems. This article presents a conceptual literature review using a systems biology approach to understand Japanese papaya as an integrated biological system in which nutritional components, secondary metabolites, and enzymatic activities interact. By positioning hydrolytic enzyme systems as the central mechanism, this review discusses the potential utilization of Japanese papaya as a biological resource and as a basis for the development of functional derivative products, including biomolecular hydrolysates. Possible applications in mechanism-based bioconversion processes are also briefly addressed.